Charting the Impacts of Media Discourses on the European Integration Project - Ana Pérez-Escoda; Tetyana Lokot (Media and Communication, 2023)
The over-exposure to information facilitated by the hybrid media system and social networks is a key factor contributing to the increasing polarization of public opinion on major political issues. The European integration project is one of the major political processes affected by information manipulation and disinformation. In this regard, social networks have become powerful tools for nurturing news siloes or “echo chambers,” influencing people’s perceptions of important political issues in a manner that could have a destabilizing effect on democratic processes and institutions. In this context, the role of media discourses and their circulation among networked publics has become particularly relevant, leading audiences to adopt different views supporting or rejecting the European project. This thematic issue features a range of articles considering how the Europeanization process is impacted by discourses circulating in the hybrid media system or threatened by the destructive dynamics of disinformation and polarization.